The concept of social obligations under Islamic law - Hj Ibrahim, Badruddin; Mohd, Azizah (Serials Publications, 2011)
This paper examines the concept of social obligations under Islamic law. It discusses the rule of obligation, one of the five types of rules under Islamic law. According to legal theorists, Islamic law is of two categories: defining law and declaratory law. The defining law is further divided, mainly, into five types of rules: obligation (ijab), recommendation (nadb), prohibition (tahrim), disapproval (karahah) and permissibility (ibahah). The paper examines the meaning of obligations, its types, rules, scope, and on whom it is incumbent. The paper also examines the objectives of Islamic law in relation to obligatory acts in realizing the public interest (maslahah) of the community particularly with respect to the protection of five essential values: religion (din), life (nafs), lineage (nasl), intellect (‘aql) and property (mal). The purpose of any rule of Islamic law is for the benefit to the people and to remove harm. This paper makes a modest attempt to provide the basic idea and understanding of the concept of social obligation in Islam.